The Effects of Melatonin and Endothelin-A Receptor Antagonist BQ-123 in Exposed to Smoke in Rat Renal Tissue. (2013) - Erdogan, Hasan; Ekici, Fatih; Aslan, Huseyin; Ozyurt, Birsen; Erdogan, Filiz; Atis, Omer
No abstract available